ANALISIS PUTUSAN HAKIM TERHADAP UPAYA HUKUM PENINJAUAN KEMBALI PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Geraldus Himawan Utomo; Yogo Pamungkas (Reformasi Hukum Trisakti, 2022)
Justice may file a PK against a PHI decision that has permanent legal force if either of the following circumstances exists, as stated in Article 57 of the PPHI Law: (1) the Supreme Court has determined a case at the cassation level; or (2) the PHI decision has permanent legal force. Legal efforts to settle industrial relations problems only go as far as the cassation level for rights disputes and job termination disputes since the passage of SEMA No. 3 of 2018. Problem statement: Does the law support the judge's decisions to grant judicial review in Decision Number 11 PK/PDT.SUS-PHI/2018 and to refuse judicial review in Decision Number 94 PK/PDT.SUS-PHl/2017? What are the legal repercussions of the judge's ruling in ruling Number 1 1 PK/PDT.SUS-PHI/2018 in favor of judicial review and the judge's ruling in ruling Number 94 PK/PDT.SUS-PHl/2017 to dismiss the PK lawsuit? Secondary data, primary data, and the normative research approach are all of a descriptive character. The release of SEMA Number 3 of 2018 is an effective move to minimize PK legal efforts in the process of settling labor disputes, according to the study's findings, debate, and conclusions.